2014
DOI: 10.1038/nchembio.1699
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibitors of the FK506-binding protein 51 by induced fit

Abstract: The FK506-binding protein 51 (FKBP51, encoded by the FKBP5 gene) is an established risk factor for stress-related psychiatric disorders such as major depression. Drug discovery for FKBP51 has been hampered by the inability to pharmacologically differentiate against the structurally similar but functional opposing homolog FKBP52, and all known FKBP ligands are unselective. Here, we report the discovery of the potent and highly selective inhibitors of FKBP51, SAFit1 and SAFit2. This new class of ligands achieves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
293
3
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 197 publications
(311 citation statements)
references
References 56 publications
9
293
3
6
Order By: Relevance
“…Introducing the analogous F67V mutation to the FK1 domains of FKBP51 and FKBP52, Hausch and colleagues (23) recently reported the development of FKBP51-selective inhibitors using Shield1 as their initial scaffold. In contrast to earlier studies on the F36V variant of FKBP12, which exhibited minimal structural perturbation upon inhibitor binding (51), Hausch and colleagues (23) found that their iFit inhibitors bound to a conformation of wild type FKBP51 and FKBP52 in which the Phe-67 side chain is reoriented away from its typical position packed underneath the tip of the ␤ 4 -␤ 5 loop (Fig. 2).…”
Section: Structural Analysis Of the Interface Between The ␤ 4 -␤contrasting
confidence: 45%
See 3 more Smart Citations
“…Introducing the analogous F67V mutation to the FK1 domains of FKBP51 and FKBP52, Hausch and colleagues (23) recently reported the development of FKBP51-selective inhibitors using Shield1 as their initial scaffold. In contrast to earlier studies on the F36V variant of FKBP12, which exhibited minimal structural perturbation upon inhibitor binding (51), Hausch and colleagues (23) found that their iFit inhibitors bound to a conformation of wild type FKBP51 and FKBP52 in which the Phe-67 side chain is reoriented away from its typical position packed underneath the tip of the ␤ 4 -␤ 5 loop (Fig. 2).…”
Section: Structural Analysis Of the Interface Between The ␤ 4 -␤contrasting
confidence: 45%
“…FKBP51-like substitutions, T58K or W60K, into FKBP52 yields a variant that binds the fluorescent iFit-FL ligand more tightly than does the wild type FKBP52 domain by over 100-fold, thus binding nearly as tightly as does FKBP51 (23). Conversely, introducing the K58T or the K60W mutation into FKBP51 markedly reduces the binding affinity for this ligand, consistent with a corresponding alteration in the stability of the conformation in the crystal structures of the iFit-inhibited protein.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…It could be possible that patients suffering from such an FKBP5 disinhibition, but presenting with distinct psychiatric symptoms, could benefit from blocking FKBP5 activity. A selective high-affinity antagonist for FKBP5 has been developed, and first experiments in experimental animals show that is has anxiolytic effects and increases stress coping (Gaali et al, 2015; Hartmann et al, 2015). …”
mentioning
confidence: 99%